1998
DOI: 10.1176/ps.49.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Practices Related to HIV Risk Assessment in General Hospital Psychiatric Units in New York State

Abstract: Semistructured interviews including (questions about practices related to HIV risk assessment were conducted on 53 psychiatric units of general hospitals in New York State in 1992 and 1993. Few units have adopted practices across the board. Assessment of risk for many or almost all patients was reported by 25 units (47 percent). On three units (6 percent) all patients received information about HIV, and on 13 (25 percent) many patients did. Twenty units (38 percent) reported counseling only a few patients abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…North American studies suggest that lack of knowledge, stigmatizing ideas and institutional barriers have limited providers' readiness to respond to HIV prevention needs in mental health settings (Herman et al, 1994;Satriano, Rothschild, Steiner, & Oldham, 1999;Walkup, Satriano, Hansell, & Olfson, 1998). Providers' age, sex, sexual orientation, and clinical experience working with HIV have been linked to their comfort in addressing HIV in some mental health care settings (Wright & Martin, 2003).…”
Section: Mental Health Care Provider Attitudes and Hiv-related Servicesmentioning
confidence: 99%
“…North American studies suggest that lack of knowledge, stigmatizing ideas and institutional barriers have limited providers' readiness to respond to HIV prevention needs in mental health settings (Herman et al, 1994;Satriano, Rothschild, Steiner, & Oldham, 1999;Walkup, Satriano, Hansell, & Olfson, 1998). Providers' age, sex, sexual orientation, and clinical experience working with HIV have been linked to their comfort in addressing HIV in some mental health care settings (Wright & Martin, 2003).…”
Section: Mental Health Care Provider Attitudes and Hiv-related Servicesmentioning
confidence: 99%
“…HIV/AIDS continue to present a major challenges for mental health professionals. Screening for risk factors may also suffer because professionals are reluctant to bring up HIV with psychiatric patients, often out of well-meaning concern for the patients [34,35]. Providers may overestimate the anxiety caused by taking a sexual history.…”
Section: Facility and Its Preparednessmentioning
confidence: 99%
“…Furthermore, Goldberg et al (2005) found that among those with serious mental illness less than half (41%) ever received HCV testing. Although there are clear guidelines and health mandates to screen for HIV and viral hepatitis (U.S. Department of Health and Human Service, 2000, 1998; Branson et al) these critical public health recommendations are not routinely provided to those with serious mental illness and are rarely implemented in the mental health systems of care (Brunette, Drake, Marsh, Torrey, & Rosenberg, 2003; Rosenberg et al, 2005; Satriano, McKinnon, & Adoff, 2007; Senn et al, 2009; Solomon et al, 2007; Swartz et al, 2003; Walkup, Satriano, Hansell, & Olfson, 1998). This is particularly important as people with serious mental illness may rely on the mental health system to provide basic medical services (Chwastiak, Rosenheck, & Kazis, 2008; Druss & von Esenwein, 2006; Druss & Newcomer, 2007; Zeber, Copeland, McCarthy, Bauer, & Kilbourne, 2009).…”
Section: Introductionmentioning
confidence: 99%